Exports and firm survival in times of COVID-19: Evidence from eight European countries - Joachim Wagner (Kiel Centre for Globalization (KCG), 2023)
This paper uses firm level data from the World Bank Enterprise surveys conducted in 2019 and from the COVID-19 follow-up surveys conducted in 2020 in eight European countries to investigate the link between exporting before the pandemic and firm survival until 2020. The estimated effect of exports is positive and statistically significant ceteris paribus after controlling for various firm characteristics that are known to be related to firm survival. Furthermore, the size of this estimated effect can be considered to be large on average. Exporting helped firms to survive.
Keywords: D22; F14; L20; L25; L29; 330; Exports; firm survival; COVID-19; World Bank Enterprise Surveys; Robit regression